2014
DOI: 10.1016/j.eplepsyres.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Medication side effects among people with epilepsy taking phenobarbital in Zambia

Abstract: Phenobarbital remains one of the most widely used antiepileptic drugs worldwide, yet there are limited data regarding side effects associated with its use in routine clinical care settings in low-income countries. Available data suggests that phenobarbital is as effective as other first-line drugs for treating tonic-clonic seizures, but side effect reports differ widely between high and low-income settings. A better understanding of phenobarbital side effect profile and severity in low-income settings is warra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…PB was once the most widely used first-line antiepileptic drug, but its use has declined in wealthy countries given a number of side effects, chiefly cognitive and functional impairments (Elafros et al, 2014). The adverse effects of PB include sedation, hyperactivity, impaired cognition, depressed mood and affect, anemia, hepatotoxicity and teratogenicity (Kwan and Brodie, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…PB was once the most widely used first-line antiepileptic drug, but its use has declined in wealthy countries given a number of side effects, chiefly cognitive and functional impairments (Elafros et al, 2014). The adverse effects of PB include sedation, hyperactivity, impaired cognition, depressed mood and affect, anemia, hepatotoxicity and teratogenicity (Kwan and Brodie, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Phenobarbital is also associated with side effects (Table 2) [40]. In addition, phenobarbital is more likely to be discontinued compared to other drugs (including carbamazepine, phenytoin, and valproate) due to its adverse reactions [44]. Due to overall limited evidence of efficacy in short-and long-term prevention of seizures as well as numerous adverse effects [44], this anticonvulsant should be used only after consideration of other therapeutic options.…”
Section: Phenobarbitalmentioning
confidence: 99%
“…This is consistent with the World Health Organization (WHO) recommendations that phenobarbital be used as first-line monotherapy in lower income settings because of its relatively low cost, convenient dosing and broad spectrum of activity (World Health Organization, 2012). However, a recent clinical study of low-income patients in Zambia reported memory problems and depression associated with use of phenobarbital (Elafros et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…More is known about the developmental neurotoxicity of phenobarbital (Verrotti et al, 2014; Bittigau et al, 2002). In rodent models, postnatal exposure to phenobarbital causes excessive neuronal apoptosis, presumably due to its GABA mimetic actions, impairs neurogenesis, causes focal mitochondrial degeneration in diverse brain regions and dysregulates the cortical proteome (Saldarriaga et al, 2014; Elafros et al, 2014; Merola and Eubig, 2012). Exposure to phenobarbital at levels that fall within the moderate to high range of clinically relevant doses impairs the morphological and physiological maturation of both excitatory and inhibitory synapses in the rodent striatum, a brain region that displays reduced volume in human imaging studies of adults exposed to AEDs early in life (National Pesticide Information Center Agency USEP, 2015).…”
Section: Discussionmentioning
confidence: 99%